Beispiel 59

  • Angabe:


    Man löse die Differentialgleichungen!


    y''' -5y'' -4y = e^2x


    Lösung:


    L...Lamda


    L^3 - 5L^2 + 8L - 4 = 0


    L1=1
    Probe: 1-5+8-4=0 => -8-8=0 => 0=0 => w. A.


    Jetzt Polynomdivison durchführen:


    (L^3 - 5L^2 + 8L - 4) / (L - 1) = L^2 - 4L + 4


    L2,3 = 2 +- Wurzel 4-4 => Doppellösung: L2,3 = 2


    => yh = c1 * e^x + c2 * e^2x + x * c3 * e^2x


    yp: Ansatz: yp = A * x^2 * e^2x


    yp' = 2Ax * e^2x + 2Ax^2 * e^2x
    yp'' = 2A * e^2x + 8Ax * e^2x + 4Ax^2 * e^2x
    yp''' = 12A * e^2x + 24Ax * e^2x + 8Ax^2 * e^2x


    A * (12-10) = 1 => A = 1/2


    yp = 1/2 * x^2 * e^2x


    => y = yh + yp => y = c1 * e^x + c2 * e^2x + x * c3 * e^2x + 1/2 * x^2 * e^2x